THE MUSICALITY OF BATANGHARI SEMBILAN: A REPRESENTATION OF SOUTH SUMATRA'S SOCIETY - Siswanto, Silo; Sunarto, Bambang; Sunarto, Budi Setiyono (Proceeding of International Conference on Art, Media, and Culture (ICAMAC), 2024)
Batanghari Sembilan Music is a term used to name a musical art form in one of the regions of South Sumatra. This art form consists of musical elements, including a type of poetry called "pantun," which is sung and accompanied by guitar. The lyrics of the pantun are in the regional language of South Sumatra. This study aims to explain the structure of the musical form of Batanghari Sembilan by examining its constituent musical elements, where the melodic structure becomes a character and style that represents the habitual behavior patterns of the South Sumatran community. Therefore, this research poses one primary question: How does the musicality of Batanghari Sembilan represent the habitual behavior patterns of the South Sumatran community? This question forms the problem statement that needs to be answered to explain aspects related to the musicality as an artistic phenomenon of Batanghari Sembilan, which depicts its supporting community.The methodology employed is a qualitative interpretative method with an emic approach, wherein the researcher understands and describes the character of Batanghari Sembilan as a cultural element by referring to the perspective of the community that owns the culture. The results of this study will elaborate and explain the musical structure of Batanghari Sembilan, which forms its regional musicality both in its musical composition and in the naming of its musical elements, representing the habitual behavior patterns of its community. Ultimately, this paper will offer an understanding of the local music of South Sumatra as a concept that has its own structure and formation, shaping its musicality